The Role of Cross-Border Post in East Nusa Tenggara in Combating Human Trafficking - Umbu Riada Tagumara Sabaora; Novriest Umbu W Nau; Indra Wisnu Wibisono (Badan Penerbit STIEPARI Press, 2025)
Human Trafficking is one of the most complex and organized forms of transnational crime, with the province of East Nusa Tenggara being one of the most vulnerable regions in Indonesia. East Nusa Tenggara geographical location, bordering Timor-Leste and having sea routes to Australia, coupled with high poverty rates and low education quality, makes the province a transit area and primary source of victims of Human Trafficking. This study aims to analyze the effectiveness of State Border Crossing Posts in combating Human Trafficking in East Nusa Tenggara, focusing on three of State Border Crossing Posts : Wini, Motaain, and Motamasin. The method used is a descriptive qualitative approach, with data collection techniques through literature review, government documents, and interviews. The findings indicate that the presence of State Border Crossing Posts has positively contributed to surveillance, awareness-raising, and economic empowerment of border communities. However, its effectiveness is still limited by structural constraints such as insufficient human resources, infrastructure, inter-agency coordination, and difficulties reaching remote areas. Additionally, the role of non-state actors such as NGOs, religious organizations, and local communities has proven to be crucial in detecting, preventing, and assisting victims of human trafficking. This study recommends enhancing cross-sectoral coordination, strengthening institutional capacity, and increasing community involvement in the cross-border protection system more comprehensively.